Deliberation-based learning: strengthening neonatal care in China. (21st September 2022) - Xiao, Yue; Qiu, Yingpeng; Husain, Lewis; Bloom, Gerald; Shi, Liwei
Abstract : This paper presents a case example from China, where detailed deliberations were instrumental in bringing together national and subnational managers to tailor implementation protocols for neonatal care strategies at provincial and county levels. The China National Health Development Research Center (CNHDRC) organised deliberations to support the formulation of strategies for improving early essential neonatal care for rural areas. The aim was to help counties, the lowest level jurisdiction in China, learn what could work locally, and to help provinces and the national government learn what should inform national policy and be disseminated widely in China's decentralised health system. It became clear that central-level stakeholders needed to learn how to help counties support the pilots. CNHDRC staff, national-level experts and academics visited pilot provinces and counties to discuss local policies, initiatives and challenges (including with patients), build a common understanding of the project and identify local support needs including by examining health records and observing health facilities. What followed were county-specific reports with priority interventions and implementation plans, which were further refined through county-level meetings. They helped central stakeholders better understand and address variations in county capacities and needs.